2013
DOI: 10.1126/science.1231077
|View full text |Cite|
|
Sign up to set email alerts
|

A Localized Wnt Signal Orients Asymmetric Stem Cell Division in Vitro

Abstract: Developmental signals such as Wnts are often presented to cells in an oriented manner. To examine the consequences of local Wnt signaling, we immobilized Wnt proteins on beads and introduced them to embryonic stem cells in culture. At the single-cell level, the Wnt-bead induced asymmetric distribution of Wnt–β-catenin signaling components, oriented the plane of mitotic division, and directed asymmetric inheritance of centrosomes. Before cytokinesis was completed, the Wnt-proximal daughter cell expressed high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
317
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(340 citation statements)
references
References 30 publications
17
317
1
5
Order By: Relevance
“…Gsk3 regulates a battery of mitotic effectors, which are required for embryonic cleavage after fertilization. Together with a body of evidence that Wnt pathway components regulate the mitotic spindle (37,39,40), our study supports the proposition that Wnt signaling orchestrates a transcription-independent mitotic program (13). It therefore seems fruitful to investigate also in somatic cells whether Wnt/STOP signaling not only regulates cell size and chromosome segregation as reported (12,40), but in addition stabilizes mitotic regulators to regulate cell cycle progression.…”
Section: Discussionsupporting
confidence: 62%
“…Gsk3 regulates a battery of mitotic effectors, which are required for embryonic cleavage after fertilization. Together with a body of evidence that Wnt pathway components regulate the mitotic spindle (37,39,40), our study supports the proposition that Wnt signaling orchestrates a transcription-independent mitotic program (13). It therefore seems fruitful to investigate also in somatic cells whether Wnt/STOP signaling not only regulates cell size and chromosome segregation as reported (12,40), but in addition stabilizes mitotic regulators to regulate cell cycle progression.…”
Section: Discussionsupporting
confidence: 62%
“…In this species, proper alignment of the spindle relies on an asymmetry in microtubule-nucleation capacity between the duplicated SPBs, which itself is correlated to centrosome age [128,129]. A similar mechanism was uncovered in animal stem cells, supporting that age asymmetry, which is inherent to the centrosome duplication cycle, is a key aspect of centrosome function [130][131][132][133][134]. This is not specific to the centrosome however, as age asymmetry between basal bodies, which underlies flagellar transformation in flagellated protists, is a key for maintaining cellular architecture through mitosis [135,136].…”
Section: Evolution Of Centrosome Function In Animalsmentioning
confidence: 74%
“…In addition, if hESCs and ISCs are in a Wnt-activated state, how can Wnt/b-catenin also influence fate decision? One potential explanation for this paradox is based on the recent observation that the directional application of a Wnt bead to one side of an ES cell can lead to preferential accumulation of b-catenin in the daughter nucleus of closest proximity (Habib et al 2013). However, if Wnts control asymmetric cell divisions in mammalian stem cells as they do in C. elegans, what defines the polarity of the Wnt signal?…”
Section: Concluding Statementsmentioning
confidence: 99%
“…Caenorhabditis elegans embryos show early signs of Wnt/b-catenin-dependent asymmetric cell divisions, which distinguish and specify the fates of early progenitors (Mizumoto and Sawa 2007;Owraghi et al 2010;Ren and Zhang 2010). More recently, it was shown that if a bead of Wnt3a is applied to one side of a murine ES cell, b-catenin will asymmetrically distribute to its two daughter nuclei (Habib et al 2013).…”
Section: Wnt Signaling and Asymmetric Cell Divisionsmentioning
confidence: 99%